Implementation of the Law on Notary Positions Concerning the Obligations of Notaries in Providing Free Legal Services in Tangerang City - Tjandraningsih, Dewi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
This research wants to know the implementation of article 37 of the notary position law number 2 of 2014 concerning the provision of free legal services. Inhibiting factors and supporting factors. Types of sociological empirical research and field research. Examining normative legal provisions in society. Conclusion The implementation of providing free legal services to underprivileged communities in the city of Tangerang has gone well. Because in general clients come to the Notary with the need to transfer rights and obligations that have economic value, and the client's desire is only to reduce costs from those set by UUJN. The supporting factors are in UU-JN and the Notary Code of Ethics. In article 37 of UU-JN, it is mandatory and binding for Notaries to provide notarial legal services, namely providing them free of charge to underprivileged people. The inhibiting factor is the notary's need to earn a living and meet the operational needs of the office. In reality, there are no legal consequences for Notaries if they cannot provide free legal services. Requirements for determining the implementation of free services to underprivileged communities by Notaries in their work areas are not regulated in UUJN or the Notary Code of Ethics